2012
DOI: 10.1111/j.1558-5646.2012.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Floral Scent and Olfactory Preferences in Pollinators: Coevolution or Pre-Existing Bias?

Abstract: Coevolution is thought to be a major factor in shaping plant-pollinator interactions. Alternatively, plants may have evolved traits that fitted pre-existing preferences or morphologies in the pollinators. Here, we test these two scenarios in the plant family of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 89 publications
2
101
0
2
Order By: Relevance
“…Modifications such as the addition of a single volatile to floral bouquets can add novel functions to it, for example changing the attractive or repellent character of floral scent bouquets (Shuttleworth & Johnson 2010;Junker, Gershenzon & Unsicker 2011;Bischoff et al 2015). In addition to innate preferences for specific volatile compounds or bouquets (Schiestl 2010;Schiestl & D€ otterl 2012), attraction to flowers often involves associative learning (Leonard, Dornhaus & Papaj 2012). Floral scent is readily learned by various flower-visiting animals, either alone or in conjunction with other floral traits (Wright & Schiestl 2009;Junker & Parachnowitsch 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Modifications such as the addition of a single volatile to floral bouquets can add novel functions to it, for example changing the attractive or repellent character of floral scent bouquets (Shuttleworth & Johnson 2010;Junker, Gershenzon & Unsicker 2011;Bischoff et al 2015). In addition to innate preferences for specific volatile compounds or bouquets (Schiestl 2010;Schiestl & D€ otterl 2012), attraction to flowers often involves associative learning (Leonard, Dornhaus & Papaj 2012). Floral scent is readily learned by various flower-visiting animals, either alone or in conjunction with other floral traits (Wright & Schiestl 2009;Junker & Parachnowitsch 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ervik and Knudsen (2003) provide a compelling argument that scarab pollination of the Nymphaeaceae (Nymphales) is a mutualistic relationship that dates to the early Cretaceous. Whether this represents an example of coevolution is unclear, and only one study has addressed this hypothesis (Schiestl and Dötterl 2012). Schiestl and Dötterl (2012) argued that volatile organic compound production/detection systems arose in the Scarabaeoidea during the Jurassic, whereas floral volatile organic compounds arose in the Cretaceous/Paleocene.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this represents an example of coevolution is unclear, and only one study has addressed this hypothesis (Schiestl and Dötterl 2012). Schiestl and Dötterl (2012) argued that volatile organic compound production/detection systems arose in the Scarabaeoidea during the Jurassic, whereas floral volatile organic compounds arose in the Cretaceous/Paleocene. This was taken as evidence that early diverging angiosperm plant/scarab associations evolved due to a preexisting sensory bias in scarabs rather than as a result of coevolution (Schiestl and Dötterl 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process has traditionally been thought of as coevolutionary, with plants also exerting selection on pollinators (Feinsinger 1983). However, more recent work in traits of attraction, color and scent has suggested that the plants have adapted their traits to sensory capabilities already present in the pollinators (Schiestl and Dötterl 2012), although there may be some fine-tuning of pollinator sensory preferences (Chittka and Menzel 1992;Raine and Chittka 2007).…”
mentioning
confidence: 99%